Suppression of Wind Waves in the Presence of Swell: A Physical Modeling Study. Issue 5 (16th May 2022) - Shabani, Behnam; Ware, Peter; Baldock, Tom E.
Abstract: Laboratory measurements of the interaction between high‐frequency (HF) wind‐waves and low frequency (LF) paddle waves are presented. The measurements were made in a wind‐wave flume with wind and paddle waves propagating in the same direction. The primary objective is to examine the physical mechanisms proposed to explain the suppression of wind‐waves due to presence of swell (here paddle waves). For this purpose, the precise time scale of the temporal transition from wind‐only to wind‐plus‐paddle conditions is examined. The results reveal that the majority of wind‐wave suppression occurs too quickly to have been caused by reduced wind‐input, instead indicating that enhanced HF wave dissipation is the primary suppression mechanism. The spatial variation in HF wave energy along the LF wave phase indicates that HF suppression mainly occurs on the LF wave crest, and high on the windward face, which are the locations that experience the highest wind velocities. This observation also suggests that the reduced wind‐input is not the primary suppression mechanism. Quantification of HF wave suppression versus a broad range of wind velocities, paddle wave conditions and fetch did not reveal any critical dependence of suppression on LF wave breaking or wind separation at LF wave crests. It is concluded that suppression occurs primarily due to enhanced dissipation of HF waves near LF wave crests. This mechanism is proposed to be coupled to the wind velocity, where an increased wind velocity near LF wave crests exceeds the level of forcing that HF waves of low C / u * can withstand without breaking. Plain Language Summary: Wind action on water surface results in generation and growth of wind‐waves. Observations have shown that the presence of swell traveling in the wind direction suppresses the wind‐waves. There is however no consensus on the physical mechanisms behind this effect. In this study, the proposed mechanisms are examined through laboratory observations of the interaction between wind‐waves and paddle waves. This includes observations of the precise transition time scale as paddle waves enter an existing wind‐wave field. The rapidity of suppression indicates that wind‐waves are actively erased by paddle waves, more so than being inhibited in their growth which is a slower process. The measurements also reveal that suppression of wind‐waves mainly occurs near the crest of paddle waves, and high on their windward face, which are the locations most exposed to the wind. Both observations indicate that enhanced dissipation of wind‐waves is the primary mechanism of their suppression, while the reduction of wind energy input to wind‐waves only plays a secondary role. The enhanced dissipation of wind‐waves is suggested to be linked to the wind velocity, with wind‐waves breaking at the crest of paddle waves as the excess wind velocity at this location exceeds the threshold the wind‐waves can withstand. Key Points: Enhanced energy dissipation is the primary mechanism behind wind‐wave suppression during interaction with swell Suppression of HF waves in the presence of LF waves mainly occurs on the LF wave crest, and high on its windward face LF wave breaking and wind separation from LF waves are not essential for HF waves suppression during swell, but may play a secondary role